Data for transcriptomic and iTRAQ proteomic analysis of Anguilla japonica gills in response to osmotic stress - Tse, William Ka Fai (Data Brief, 2015)
This article contains data related to the two research articles titled Transcriptomic and iTRAQ proteomic approaches reveal novel short-term hyperosmotic stress responsive proteins in the gill of the Japanese eel (Anguilla japonica) (Tse et al. [1]) and iTRAQ-based quantitative proteomic analysis reveals acute hypo-osmotic responsive proteins in the gills of the Japanese eel (Anguilla japonica) (Tse et al. [2]). The two research articles show the usefulness of combining transcriptomic and proteomic approaches to provide molecular insights of osmoregulation mechanism in a non-model organism, the Japanese eel. The information presented here combines the raw data from the two studies and provides an overview on the physiological functions of fish gills.